Introduction to Algebraic Thinking in 3 Years: Identification of Qualitative and Quantitative Change - Fuentes, Sandra; Cañadas, María C.; Anglada, M° Lourdes (Uniciencia, 2026)
This study is part of a broader research project on algebraic thinking in early childhood and elementary education (www.pensamientoalgebraico.en). [Objective] The objective of this work is to identify the change perceived by 3-year-old children when solving generalization tasks that involve qualitative or quantitative changes. [Methodology] A teaching experiment consisting of 4 work sessions with a group of 25 3-year-old children from a public school in Granada was designed and implemented. The perception of qualitative and quantitative change was investigated. The first session involved color and size as attributes; the second session included the function f(n)=n+1. The focus was on identifying relationships between variables and on the way children expressed these relationships through the changes that affect these variables. [Results] The children identified the qualitative change by saying that the colored object that entered the rocket changed color and came out gray, for example, they used expressions such as “the color is gone,” “it comes out black,” or “it comes out gray.” In the case of quantitative change, they indicated that the ice cream that was inserted always came out with one more scoop than those that entered the machine, using statements such as “it comes out bigger,” “it comes out higher,” or “many come out.” [Conclusion] Based on the statements given by the children, it can be concluded that they identified the changes in color, size and increase.